Na busca da afirmação do direito a saúde indígena: os efeitos da implementação da portaria ministerial n.º 2656 de 2007 em municípios do Paraná - Abreu, José Carlos Silva de (2012)
The changes in the Health System Act implemented the Indigenous Health Care Subsystem, which brought to attention a series of discussions about the capabilities of the State to establish a health care system which respects the ethnic and cultural characteristics of the said people. To this purpose, the Ministry of Health and the Health National Foundation published a series of ordinances, among them the Ministry Ordinance (MO) n.o 2656/2007, which defines the institutional roles of the government bodies and regulates the transfer of funds to indigenous health programs, but there have been few studies to evaluate the results so far. The general aim of the present study is to analyse the implementation of the responsibilities as established by the MO 2656/2007 to the local governments and the repercussions for the indigenous health care in the State of Paraná and will attempt at showing the way government bodies and other agents have been interacting towards the organization of the indigenous health care services and identifying factors which promote or hinder the implementation of the said MO. This is a qualitative study, characterized by both an exploratory and documental nature, whose target study group was formed by 13 municipalities which had the task of articulating the health services in the settlements with the Brazilian Universal Healthcare Program (SUS). The results show that the MO implementation process neither altered the status quo nor enabled a better integration among the government bodies. The indigenous health care planning process was not integrated, thus hindering the establishment of goals which ensured the integrity of the program. The difficulties in the execution of the program are still present and there are no significant changes in the current standard health care model. There are problems in the articulation of the standard network with other instances within the SUS and the human resources did not get the appropriate training. There are elements which can lead to success, though, like the upkeep of the regular transfer of funds, the experience acquired in more than 10 years by the municipalities and the means which enable an integrated planning, but which have not yet been used to the fullest. It is possible to conclude that the role of the municipality has to be reviewed, and it should encompass what is established by the SUS, that is, full responsibility for the management of the health programs for all the people in its area, where the principles of integrity and equality encompass the different, as a sine qua non condition to the universal right to health access.